Relasi Agama dan Negara dalam Perspektif Hukum Tata Negara Islam di Era Negara Modern - Sahruni Sahruni; Dhiyaul Akbar; Kurniati Kurniati (Indo Publishing, 2026)
This study examines the relationship between religion and the state from the perspective of Islamic Constitutional Law in the modern state era. It employs a normative legal research method using conceptual and statutory approaches, supported by secondary data obtained through library research. The findings reveal that the relationship between religion and the state in Islamic Constitutional Law is constructed upon three main paradigms: integralistic, symbiotic, and secularistic. Operationally, this relationship is implemented through the concept of siyasah shar’iyyah, which integrates Islamic values into the functions of legitimacy, supervision, legislation, and judiciary, all oriented toward public welfare (maslahah). In the context of the modern state, the application of Islamic Constitutional Law is substantive and contextual, emphasizing the internalization of values such as justice, public interest, and respect for human rights into the national legal system without requiring the formal establishment of a religious state. Therefore, the relationship between religion and the state can be realized in a harmonious, inclusive, and adaptive manner in line with the principles of democracy and pluralism.